Alkylation of Free Thiol Groups During Extraction: Effects on the Osborne Fractions of Wheat Flour. Issue 3 (5th December 2016) - Schmid, Markus; Wieser, Herbert; Koehler, Peter
Abstract : Wheat proteins are classified according to solubility into the so‐called Osborne fractions. Because wheat flour contains both free thiol and disulfide groups, thiol–disulfide interchange reactions are possible during extraction. Osborne fractionation of 12 different wheat flour samples was performed in the presence of N ‐ethylmaleinimide (NEMI) to alkylate free thiol groups and without addition of NEMI (control). The addition of NEMI during extraction tended to decrease the content of gliadins (predominantly α‐gliadins) and caused an increase of the content of glutenins in most flour samples. Thus, alkylation of free thiol groups during extraction led to a decline of the gliadin/glutenin ratio from 2 (control) to approximately 1.5 (NEMI). NEMI and control gliadins were separated by gel‐permeation HPLC into an oligomeric subfraction (high‐molecular‐weight [HMW] gliadins) and two monomeric subfractions. In most flours (8 of 12), the addition of NEMI led to a significant increase of the content of HMW gliadins. HMW gliadins from cultivar Akteur wheat were preparatively isolated from NEMI and control gliadins and characterized by HPLC, sodium dodecyl sulfate polyacrylamide gel electrophoresis, and N‐terminal sequencing. HMW gliadin isolated in the presence of NEMI had a significantly higher content of low‐molecular‐weight glutenin subunits and disulfide‐bound cysteine as well as a lower content of α‐gliadins and disulfide‐bound glutathione compared with the control.